Pengaruh Disiplin Kerja Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Timor Otsuki Mutiara di Desa Wolwal Barat Kecamatan Alor Barat Daya Kabupaten Alor - Lely Kinanggi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the effect of work discipline, workload and work environment on the performance of employees of PT Timor Otsuki Mutiara, Wolwal Barat Village, Alor Barat Daya District, Alor Regency. The samples taken in this study were using a saturated sampling technique with a total sample of 40 people. The collection techniques were observation, interviews, questionnaires and literature study. By using the T test and F test which answer the research problem. Partially Work Discipline affects the Performance of PT Timor Otsuki Mutiara Employees in Wolwal Barat Village, Alor Barat Daya District, Alor Regency, Workload affects PT Timor Otsuki Mutiara Employee Performance in Wolwal Barat Village, Alor Barat Daya District, Alor Regency, Work Environment influences Employee Performance PT Timor Otsuki Mutiara in West Wolwal Village, Alor Barat Daya District, Alor Regency. Work Discipline, Workload, and Work Environment Together on Employee Performance at PT Timor Otsuki Mutiara In West Wolwal Village, Alor Barat Daya District, Alor Regency, Great Influence of Work Discipline, Workload, and Work Environment Together on Employee Performance at PT Timor Otsuki Mutiara Di Wolwal Barat Village, Alor Barat Daya District, Alor Regency is 44.8% "